Privatisation in Developing Countries: What Are the Lessons of Recent Experience? - Saul Estrin; Adeline Pelletier (Institute for the Study of Labor (IZA), 2016)
This paper reviews recent empirical evidence on privatisation in developing countries. Particular emphasis is placed on new areas of research such as the distributional impacts of privatisation. Overall, the literature now reflects a more cautious and nuanced evaluation of privatisation. Thus it is found that private ownership alone does not automatically generate economic and employment gains in developing economies; pre-conditions (especially the regulatory infrastructure) and the process of privatisation are important to attain a positive impact. Such factors include well-designed and sequenced reforms; the implementation of complementary policies; the creation of regulatory capacity; attention to poverty and social impacts; and strong public communication; a list which is often challenging in developing countries. However, the studies do identify scope for efficiency-enhancing privatisation which also promotes equity in developing countries.
Keywords: L1; L51; O10; 330; impact of privatisation; economic reforms; developing economies; regulation; distribution of income